(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Anthropometric measurements of the human head serve as critical indicators for assessing growth patterns, developmental status, and health risks in pediatric populations. This study evaluates the head size parameters of school-aged children living in rural settlements of the Tashkent Region. A total of 420 children aged 7 to 15 years were examined using standard anthropometric techniques. The study revealed age- and sex-related differences in head circumference, head length, and head breadth, reflecting normal growth trends and highlighting slight regional variations. The findings can contribute to the development of updated reference norms for Uzbek schoolchildren and assist in early identification of craniofacial deviations.